Dificuldades na efetivação do Programa Dinheiro Direto nas escolas nas instituições de ensino básico do Brasil - EVANGELISTA, Shirley Rolim (2020)
This article aimed to analyze the importance of the PDDE in financing the improvement of the infrastructure and pedagogical practices of public schools in Brazil. What problems are left unresolved in schools when the resource from the PDDE does not reach them? Among the State and Municipal education networks which present more prevalence and absence in value from the PDDE? In the scope of these institutions, what is the value corresponding to each student according to the enrollments made? The study was supported by bibliographic research based on the authors: ADRIÃO; PERONI (2007), CARDOSO (2009), MAFASSIOLI (2015) and FERREIRA; GOMES; LIMA (2017). The documentary research had data extracted from the website National Fund for Education Development (FNDE) - List of executing units served by PDDE. This study had a theoretical background in authors who worked on the PDDE theme from 2007 to 2017, and part of this interval referred to the operational difficulties of PDDE in the municipality of Igarapé-Miri - Pará in the years 2015 to 2017. The result showed that schools State in operation in this municipality, face operational difficulties in receiving the PDDE resource, when compared to the schools of the municipal system of that city, which presented higher prevalence in receiving this financial contribution, considering the years of study submitted to the analysis.